Diurnal Variation of Phytoplankton and Related Ecological Parameters of One Location in Habbaniya Lake, Iraq - AL-Ghafily, A. A. k.; Al-Tamimi, A.N.A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The presnty study included physical , chemical  and phycological study of choosen one station in  Habbaniya lake to investigat the diurnal variation at each hour along the 24 hours . Water temperature showed clear variations and coincided with the air temperature of study , Habbaniya Water was alkaline with pH more than 7 without clear diurnal variations . Conductivity , Total hardness , Calcium and Magnesium values showed no clear varitions . Chloride and Salinity values appeared relatively stable . The data showed a relative increasing in Dissolve oxygen values during the night hours.On the other hand the alkalinity and acidity values were unstable during the 24 hours of the study. According to the quantitative study of algae (20) genera of them were recorded , (9) of them belonged to Bacillariophyceae , (7) to Cyanophyceae , (3) to Chlorophyceae and one genus belonged to Euglenophyceae , . The total cell count of algae ranged between (217- 477)Ã—10Â³ cell/l , The genera Cyclotella , Naviculla , Botrycocus and Oscillatoria were recorded at all hours of sampling